Analysis of Factors Influencing the Income of Women Informal Sector Workers in Indonesia (IFLS Data Analysis 5) - Suripto Suripto; Anandito Wicaksono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted with the aim of being able to find out the factors that influence the income of women informal sector workers in Indonesia in 2014 based on data from the 2014 batch 5 Indonesian family life survey (IFLS-5). IFLS 5 data is the latest data conducted by several institutions. such as rand meters, survey meters and the demographic institute of the Faculty of Economics and Business, University of Indonesia (LD FEB UI). Based on the existing problems, namely female workers contribute 38% of the total national workforce and the informal sector absorbs the highest workforce in Indonesia, which is equal to 69%, but it is ironic because the informal sector has the lowest income level compared to other sectors. This study took a sample of 2,294 respondents taken from 13 provinces in Indonesia. Respondents were filtered based on age with a range of 15-65 years. With the dependent variable income of women workers and the independent variables education level, age, marital status, working hours, work experience and job training. From the results of statistical tests conducted, it shows that 31% of the independent variables partially affect the dependent variable, and the rest are influenced by independent variables outside the research model. The results of multiple linear tests show that the independent variables of education level, age, working hours, work experience and job training are significantly independent variables that can explain the effect on the variable income of women informal sector workers in Indonesia. Keywords: IFLS-5, Female Workforce, Income of Informal Sector Female Workers.